Space and Theatre - Carlson, Marvin (FOCUS: Papers in English Literary and Cultural Studies, 2012)
Theatre as an artistic and cultural activity has been the subject of academic speculation ever since the Greeks, but it was not until the beginning of the nineteenth century that European and American scholars institutionalized a field of theatre studies. A significant part of this new field’s self-definition involved a clear splitting away from traditional literary studies, within which theatre had previously had its academic home. The entire Western tradition, from the Greeks onward, considered the drama primarily as a branch of literature—the other basic divisions being the epic and the lyric. Traditionally theatre scholarship was based upon the literary text (Artistotle’s indifference to spectacle is an early and notorious example of this bias) and the actual process of the physical realization of this text, while not entirely ignored, was a matter of considerably less interest.